Universals of causative and anticausative verb formation and the spontaneity scale - Haspelmath, Martin (Lingua Posnaniensis, 2016)
In this paper, I formulate and explain a number of universal generalizations about the formation of causative verbs (overtly marked verbs with causal meaning) and anticausative verbs (overtly marked verbs with noncausal meaning). Given the “spontaneity scale” of basic verb meanings (transitive > unergative > automatic unaccusative > costly unaccusative > agentful), we can say that verb pairs with a noncausal verb higher on the scale tend to be causative pairs, and verb pairs with a noncausal verb lower on the scale tend to be anticausative pairs. I propose that these generalizations can be subsumed under form-frequency correspondence: That transitive base verbs tend to form causatives (often analytic causatives) is because they rarely occur in causal contexts, and the fact that unaccusative verbs tend to be coded as anticausatives is because they frequently occur in causal contexts, and special marking is required for the rarer and less expected situation.